PROBLEMS IN ROLE NEGOTIATION AND DECISION-MAKING IN A PSYCHIATRIC TEAM - Dixon, Charles L. (My University, 1980)
The thesis is a study of two psychiatric teams, one adult, the other adolescent, working in an out-patient facility in the same psychiatric hospital. The teams are analyzed with respect to their decision-making ability and the extent to which their functioning is a reflection of the hospital system. The two research questions posed are directed at team interaction and team-hospital relations. The research questions are: 1) How do role negotiations effect team decision-making? 2) Is team functioning a reflection of the hospital system? In regard to question (1), the literature supports the view that the main task of an interdisciplinary team is to make negotiated rather than unilateral decisions. Decisions should reflect the inputs from all members of the team. The psychiatric teams, being interdisciplinary, should negotiate to develop alternatives based on guiding criteria from all disciplines. A team decision involves choosing the best alternative presented in the context of an appropriate therapeutic or administrative goal. In respect to question (2), it will be argued that, since the teams are sub-systems of the larger hospital system, they are in a dependent relationship to it. As such, they tend to reflect to a large extent its main characteristics, especially with regard to modes of decision-making. That is, if the hospital makes unilateral decisions, the teams will reflect this tendency. In the examination of both questions, the sociological perspectives of symbolic interaction and general systems theory are employed as they seem to provide a reasonable framework for analyzing the data. To gather the data, tape recordings of consecutive team meetings and interviews with members of both teams were made in conjunction with documentary analysis. The ability to make team decisions involves some understanding of the negotiation process and it appears from the study that members lack such skills. It is also evident that the closed hospital system undermines the climate for negotiations. Consequently, it would not be sufficient to merely develop team decision-making skills without at the same time changing the present closed hospital system to accommodate a more open team system. Initially, to bring about desired changes on the teams, an in-service training program is required which would not only increase cognitive skills for team decision-making, but would also motivate members to use these skills once they are acquired. To lend some support to the proposed changes on team functioning, the hospital system of which the team is a part should also be changed, given the reciprocal nature of their relationship. A less rigid and authoritarian hospital organizational structure might help to encourage the maturation of a more open team system where members would negotiate to reach team decisions. Out of this kind of inter-disciplinary decision-making might evolve a non-medical model of therapeutic intervention which assumes that adequate mental health services can be provided by all the mental health professional including the psychiatrist, all working together as equals. In making recommendations for change it is helpful if the change agent appreciates that both systems, the team and the hospital must be encouraged to change together since they are in a reciprocal relationship. So, in the implementation of any meaningful innovation he would need the active participation of team members as well as those in the hospital hierarchy. Also, since sudden changes would probably be resisted perhaps at all levels of the organization, the change agent would have to be satisfied with facilitating incremental change or step by step implementation and in this way insure gradual incorporation of the proposed changes into both systems.
Keywords: Education; Education